Cooperation networks: a tool to minimize gender inequalities in science - Esther Torrado Martín-Palomino; Ana M. González Ramos (Feminismo/s, 2017)
The triumphalist messages on the incorporation of women in scientific fields however, it hides an invisible reality that only the feminist studies have addressed and displayed evidence. These studies provide analytical perspectives that reveal complex relationships between women and men shaping by male perspective of the power structures. A critical examination will reveal that formal equality does not yield real equality and, on the contrary, justifies the current discrimination based on gender. Objectivity and meritocracy veils men and women inequalities in science. This article focuses on the analysis of the situation of women researchers and the strategies to pursue high goals in their careers. In that sense, we analyze the usefulness of cooperation networks, institutional such as equality units, gender, or informal where a group of women capitalizes on their experience, through information or emotional support for other women’s benefits. For developing this argument, we are based on different bibliographic sources, the results of the survey of 700 women and men who perform research in universities and research centers, and ten case studies carried out in the project Genera: Generation of a more inclusive and competitive knowledge economy. The findings show that it is not the unique strategy, the networks based on sorority and cooperation provide advantages to improve achievements and to reduce personal costs of pursuing a high competitive career shaping by male-dominated structure of power.